POSSIBILITIES FOR THE DISAPPEARANCE AND PRESERVATION OF THE WISDOM TOOTH IN MODERN DENTISTRY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The main goal of this study is to study the reasons for the loss of wisdom teeth in modern dentistry and the ways of preserving them. The tasks of the research are to determine the evolutionary significance of the wisdom tooth, analyze its role and significance in modern dentistry, and recommend effective methods for preserving wisdom teeth based on innovative technologies. To study the anatomy and functional properties of the wisdom tooth, an analysis of the methods, technologies and approaches used in the research was carried out. Innovative approaches to the treatment of wisdom teeth were analyzed, based on modern dental diagnostic methods, including radiography and 3D modeling technologies. Experimental studies have examined the need to remove wisdom teeth and the possibilities of preserving them. According to the results, with the help of modern technologies, it is possible to restore the functional state of wisdom teeth through effective preservation methods, including orthodontic interventions and therapeutic treatments. The final phase of the study developed scientific and practical recommendations for dentists when deciding whether to remove or retain a wisdom tooth.